2012
DOI: 10.1016/j.applthermaleng.2012.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of energy performance of modified single-stage CO2 transcritical vapour compression cycles based on vapour injection in the suction line

Abstract: Abstract.This work presents the experimental evaluation of the energy performance of a modified single-stage CO 2 transcritical refrigeration plant with an internal heat exchanger (IHX) based on vapour injection in suction line. This modification, which is only applicable to refrigeration plants with an expansion process divided in two stages with a liquid receiver between them, consists of extracting saturated vapour from the liquid receiver in order to: decrease the vapour quality at the evaporator inlet, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 13 publications
0
9
0
3
Order By: Relevance
“…Others analysed experimentally the effect of vapour extraction from the vessel to inject it in different points of the refrigeration cycle. The improvements of COP reached up to 7% in single-stage cycles (Cabello et al, 2012) and 16.5% in double-stage plants (Cho et al, 2009). Other improvements are the use of expanders (Li et al, 2004;Yang et al, 2007) and ejectors (He et al, 2014;Lee et al, 2014) to reduce irreversibilities during the expansion process, which also offered COP increments.…”
Section: Introductionmentioning
confidence: 97%
“…Others analysed experimentally the effect of vapour extraction from the vessel to inject it in different points of the refrigeration cycle. The improvements of COP reached up to 7% in single-stage cycles (Cabello et al, 2012) and 16.5% in double-stage plants (Cho et al, 2009). Other improvements are the use of expanders (Li et al, 2004;Yang et al, 2007) and ejectors (He et al, 2014;Lee et al, 2014) to reduce irreversibilities during the expansion process, which also offered COP increments.…”
Section: Introductionmentioning
confidence: 97%
“…The experimental measurements demonstrated that the IHX can improve the COP up to a maximum of 10 %. Others analyzed the effect of extracting vapour from the intermediate vessel to be injected in different points of the cycle, measuring maximum increments of 7 % in single-stage plants (Cabello et al, 2012) and 16.5 % in double-stage cycles (Cho et al, 2009). The use of expanders (Li et al, 2004), ejectors (Lee et al, 2014) and regulation strategies (Peñarrocha et al, 2014) are also considered.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results showed that the IHX reduces the ejector contribution to the system performance. Cabello et al (2012) presented an experimental analysis of the energetic performances of a modified single-stage CO 2 trans-critical refrigeration plant with an IHX based on vapor injection in suction line. Three different injection points have been evaluated experimentally.…”
Section: Introductionmentioning
confidence: 99%